Adoptive Transfer of Renal Allograft Tolerance in a Large Animal Model. Issue 1 (10th August 2015) - Villani, V.; Yamada, K.; Scalea, J. R.; Gillon, B. C.; Arn, J. S.; Sekijima, M.; Tasaki, M.; Cormack, T. A.; Moran, S. G.; Torabi, R.; Shimizu, A.; Sachs, D. H.
Abstract : Our recent studies in an inbred swine model demonstrated that both peripheral and intra‐graft regulatory cells were required for the adoptive transfer of tolerance to a second, naïve donor‐matched kidney. Here, we have asked whether both peripheral and intra‐graft regulatory elements are required for adoptive transfer of tolerance when only a long‐term tolerant (LTT) kidney is transplanted. Nine highly‐inbred swine underwent a tolerance‐inducing regimen to prepare LTT kidney grafts which were then transplanted to histocompatible recipients, with or without the peripheral cell populations required for adoptive transfer of tolerance to a naïve kidney. In contrast to our previous studies, tolerance of the LTT kidney transplants alone was achieved without transfer of additional peripheral cells and without strategies to increase the number/potency of regulatory T cells in the donor. This tolerance was systemic, since most subsequent, donor‐matched challenge kidney grafts were accepted. These results confirm the presence of a potent tolerance‐inducing and/or tolerance‐maintaining cell population within LTT renal allografts. They suggest further that additional peripheral tolerance mechanisms, required for adoptive transfer of tolerance to a naïve donor‐matched kidney, depend on peripheral cells that, if not transferred with the LTT kidney, require time to develop in the adoptive host. Abstract : Tolerated renal allografts contain a potent tolerance‐inducing and/or ‐maintaining cell population sufficient for adoptive transfer of tolerance to a naïve recipient.